The value of magnetic resonance imaging in assessing the circumferential resection margin of rectal cancer - Ha, Pham Hoang; Trong, Nguyen Minh; Hung, Nguyen Xuan; Thai, Pham Quang (Tạp chí Nghiên cứu Y học, 2025)
This study evaluated the value of magnetic resonance imaging (MRI) in assessing the circumferential resection margin (CRM) and lymph node metastasis in rectal cancer. This cross-sectional study, conducted at Viet Duc University Hospital between October 2016 and May 2019, involved 109 rectal cancer patients, who underwent rectal resection after receiving pre-operative MRI staging. The correlation between preoperative MRI and postoperative histological analysis was evaluated regarding CRM invasion, the distance from the tumor or metastatic lymph node to the mesorectal fascia, the tumor stages (≤ T3, > T3), and lymph node metastasis. MRI had an accuracy of 86.2% in predicting invasive CRM with a sensitivity of 65.0%, a specificity of 91.0%, a positive diagnostic value of 61.9%, and a negative diagnostic value of 92.1%. Regarding the diagnosis of metastatic lymph nodes, MRI showed an accuracy of 50.5%, a sensitivity of 88.6%, and a specificity of 24.6%, the positive diagnostic value was 44.3%, while the negative diagnostic value was 76.2%. These results indicate a strong correlation between the performance of MRI and pathology for diagnosis of CRM invasion. When detecting metastatic lymph nodes, MRI exhibited higher sensitivity at the expense of lower specificity.